Redesain Gedung Pasar Keputran Surabaya Berdasarkan SNI Pasar Rakyat 8152:2021 - Oktaviani, Nadila (Jurnal Vokasi Teknik Sipil, 2023)
Keputran Market, which is one of the largest main markets in Surabaya, provides basic needs and household needs for the community. Currently, the condition of the Keputran Market is considered very lacking, especially when compared to the modern market with various comfort offerings. Irregular trade areas, poor circulation management, and inadequate infrastructure are some of the problems in Pasar Keputran. This problem underlies this research with the aim of rearranging the structure of the Pasar Keputran Building to provide physical changes without changing the function of the building in accordance to SNI Pasar Rakyat regulation 8152:2021. This quantitative research uses observation, interview, and literature methods as data collection techniques. The collected data that was analyzed resulted in a redesign of the Pasar Keputran building in the form of adding a floor intended to provide facilities in the form of parking and loading areas on the ground floor, the addition of several supporting spaces, merchant zoning arrangements that are differentiated based on the type of commodity, and the addition of accessibility in the form of ramps and special bathrooms for people with disabilities. Based on the results of preliminary calculations of the building structure, the dimensions of the columns used were 50 cm / 50 cm, the main beam 25 cm / 50 cm, the child beam 20 cm / 40 cm, the plate thickness 12 cm, the sloof 20 cm / 40 cm, and the concrete deck combination with the spandex canopy roof using a steel frame as the roof plan.